Teaching Index Numbers to economists - Robert O'Neill (Cogent Economics & Finance, 2015)
Economic statistics are frequently reported in the form of index numbers. This article considers how the field of Index Numbers should be approached in the teaching of a general economic degree. While the topic finds a natural home in statistics modules, it is emphasised that the area can also be referred to in the teaching of other areas of economics. It is also emphasised that the differences between Index Numbers theory and the practice of compiling economic statistics such as inflation can help students gain a better understanding of applied economic statistics. Methods for assessing learning in the area are also considered and available material to support teaching is also summarised.
Keywords: 330; Index Numbers; economic statistics; official statistics; inflation; economic tools for teaching